The failure of the symbolic order in shaping the female subject in Adrienne rich's Aunt Jennifer Tigers - Hassan, Mohamad Fleih; Talif, Rosli; Hardev Kaur, (Malaysian Association of Modern Languages, 2016)
Adrienne Rich was one of the leading feminist voices who called for the re-establishment of the feminist discourse away from the bigotry of the patriarchal thought. In her early stage of writing, Rich imitated the styles and subject matters of the great male writers of the literary scene. Therefore, the female characters in her early poems didn’t find the appropriate signifiers that express their voices in the masculine symbolic language they used. They tried to revolt but in vain because the masculine symbolic language gave no space to the circulation of female needs and desires. As such, the objective of this paper is to examine the failure of the symbolic order in the construction of the female subject in Adrienne Rich’s Aunt Jennifer’s Tigers. However, the study is conducted in the light of Kristeva’s the Symbolic and the Semiotic (1984). Kristeva thinks that these two modalities are completing each other in the dynamic signifying process needed for the constitution of the Subject, and that the failure of reflecting the semiotic in the symbolic results in the destabilization of the subject. Thus, the study concludes that the female subject in Aunt Jennifer’s Tigers suffered the duality of living due to the failure of interaction between the symbolic and semiotic as two modalities of signification, which led to the destabilization of Aunt Jennifer’s subject and the domination of the symbolic order.